2014
DOI: 10.1542/peds.2014-1699
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Use in Caries Prevention in the Primary Care Setting

Abstract: Dental caries remains the most common chronic disease of childhood in the United States. Caries is a largely preventable condition, and fluoride has proven effectiveness in the prevention of caries. The goals of this clinical report are to clarify the use of available fluoride modalities for caries prevention in the primary care setting and to assist pediatricians in using fluoride to achieve maximum protection against dental caries while minimizing the likelihood of enamel fluorosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
83
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 24 publications
0
83
0
6
Order By: Relevance
“…33 Furthermore, the American Academy of Pediatrics recommends that children begin having their teeth cleaned twice daily using a rice grain size amount of fluoride toothpaste at the first tooth eruption. 34 At 3 years of age, the amount of fluoride toothpaste should be increased to a pea-sized amount. In addition to using fluoride toothpaste, children (including those with CL/P) should drink optimally fluoridated water, where available, and receive at least twice-yearly fluoride varnish applications beginning with the first tooth eruption.…”
Section: Oral Health and Dental Carementioning
confidence: 99%
“…33 Furthermore, the American Academy of Pediatrics recommends that children begin having their teeth cleaned twice daily using a rice grain size amount of fluoride toothpaste at the first tooth eruption. 34 At 3 years of age, the amount of fluoride toothpaste should be increased to a pea-sized amount. In addition to using fluoride toothpaste, children (including those with CL/P) should drink optimally fluoridated water, where available, and receive at least twice-yearly fluoride varnish applications beginning with the first tooth eruption.…”
Section: Oral Health and Dental Carementioning
confidence: 99%
“…The fluoride from mouth rinse is held in dental plaque and saliva and averts tooth decay [22,23]. An over-the-counter solution of 0.05% sodium fluoride (230 ppm fluoride) for day by day flushing are accessible for use by people more established than six years of age [22,24,25]. The use in people more youthful than six years old isn't suggested in light of the danger of fluorosis if the wash is repeatedly gulped [23,25].…”
mentioning
confidence: 99%
“…An over-the-counter solution of 0.05% sodium fluoride (230 ppm fluoride) for day by day flushing are accessible for use by people more established than six years of age [22,24,25]. The use in people more youthful than six years old isn't suggested in light of the danger of fluorosis if the wash is repeatedly gulped [23,25]. Higher quality mouth rinses (e.g., 0.2% impartial sodium fluoride to be utilized once per week) for those at high danger of tooth rot must be recommended by a dental specialist or physician [25].…”
mentioning
confidence: 99%
“…12 Thus, there has been substantial public and professional debate about f luoride, and myriad information is available, often with confusing or conf licting messages. 12 Therefore this study explored other alternatives for subsitution of fluoride alone.…”
mentioning
confidence: 99%
“…12 Thus, there has been substantial public and professional debate about f luoride, and myriad information is available, often with confusing or conf licting messages. 12 Therefore this study explored other alternatives for subsitution of fluoride alone. Previous study demonstrated that calcium contained in yogurt, which are daily comsumed by Australian, have an inhibitory effect on demineralization and promote the remineralization of dental enamel.…”
mentioning
confidence: 99%